A species continuum exists between Pseudomallada prasinus and P. abdominalis (Neuroptera, Chrysopidae) - Duelli, Peter; Henry, Charles S. (Zootaxa, 2020)
It has recently been determined that Pseudomallada prasinus (Burmeister, 1839) is part of a complex of prasinoid species (Duelli & Obrist, 2019). Apart from P. prasinus s.s. and P. abdominalis s.s., each at the opposite end of the prasinoid spectrum, some populations in Switzerland and surrounding countries show consistently differing morphological and biological traits, while nevertheless living in the same habitats. To test whether they constitute reproductively isolated species, seven strains of three morphologically distinctive prasinoid morphs (Pp1, Pp2, Pp3) were reared and the virgin offspring (F1) paired with single partners of each of the six other strains. The four strains of morph Pp3 were unable to produce any viable offspring when paired with the two other morphs, suggesting that Pp3 is a distinct species. The Mediterranean morph Pp1 produced some offspring with the two strains of morph Pp2, but the crossed offspring (F2) of the hybrids yielded less than 2% viable larvae. Furthermore, in a cage experiment with free choice of partners between Pp1 and Pp2, all females produced offspring of their own morph; there were no hybrids. We conclude that north and south of the Alps there are at least three reproductively isolated prasinoid species in addition to P. prasinus and P. abdominalis. Their distinctiveness is principally based on live color traits, but also on the presence or absence of the “furwing” phenotype in males (double number of setae on wing veins). Therefore, many old museum specimens, especially females, cannot be identified with confidence. Because most of the dozens of synonymized type specimens of prasinoid species and varieties in museums are females, and all have lost their color, it is presently not possible to assign valid names to the three “new” species. We call them Pseudomallada prasinoid 1 (Pp1), P. prasinoid 2 (Pp2), and P. prasinoid 3 (Pp3). Using the distinctive traits given here, most specimens that have retained their original colors (live, recently pinned, or deep frozen) can be identified.